DAMPAK PERTAMBANGAN NIKEL TERHADAP LINGKUNGAN DI KABUPATEN HALMAHERA TENGAH - Anhar Drakel (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
Nickel mining is considered a crucial activity in the transition from fossil fuels to renewable energy in the transportation sector. However, nickel mining activities negatively impact the entire ecosystem, both upstream and downstream, potentially impacting the environmental and socioeconomic conditions in Central Halmahera Regency. Along with the development of industrial development, it has an impact on water quality, both surface water and groundwater and even coastal areas are experiencing changes. Even a number of rivers are buried and no longer flow to the sea. The objectives of this research are as follows: (1). To determine the effect of drought on the ecosystem. (2). To determine the effect of technology on the ecosystem. (2). To determine the effect of biodiversity on the ecosystem. Based on the analysis results, it was found that drought, technology and biodiversity jointly influence the ecosystem in the environment, both upstream and downstream.